Dynamic Architecture for Data Replica Balancing in HDFS: Stability, Efficiency, and Data Locality Evaluations - Fazul, Rhauani Weber Aita; Mendizabal, Odorico Machado; Barcelos, Patrícia Pitthan (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2024: Anais do XLII Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2024)
Hadoop Distributed File System (HDFS) is known for its specialized strategies and policies tailored to enhance replica placement. This capability is critical for ensuring efficient and reliable access to data replicas, particularly as HDFS operates best when data are evenly distributed within the cluster. In this study, we conduct a thorough analysis of the replica balancing process in HDFS, focusing on two critical performance metrics: stability and efficiency. We evaluated these balancing aspects by contrasting them with conventional HDFS solutions and employing a novel dynamic architecture for data replica balancing. On top of that, we delve into the optimizations in data locality brought about by effective replica balancing and their benefits for data-intensive applications.